The safety of pericardiocentesis in patients under antithrombotic therapy: A single-center experience - Zhu, Yuansong; Zhang, Chengxiang; Xie, Yuqiao; Sasmita, Bryan Richard; Xiang, Zhenxian; Jiang, Yi; Gong, Ming; Wang, Yaxin; Chen, Siyu; Luo, Suxin; Huang, Bi (Frontiers in Cardiovascular Medicine, 2022)
Objective: This study aimed to analyze the characteristics of patients with pericardial effusion requiring pericardiocentesis and to evaluate the safety of pericardiocentesis without discontinuation of anticoagulant or antiplatelet drugs. Methods: We performed a retrospective study of patients undergoing pericardiocentesis in our hospital between 2012 and 2022. Patients were categorized into the Antithrombotic Group if they had used any antiplatelet or anticoagulant drugs on the day of pericardiocentesis; otherwise they were categorized into the Non-antithrombotic Group. All procedures were performed by experienced cardiologists with echocardiographic guidance. Bleeding events were defined using the National Institutes of Health scale of adverse events. Results: A total of 501 consecutive patients were identified and 70 cases were under antithrombotic drugs (Antithrombotic Group). Patients in Antithrombotic Group were older, had more comorbidities, presented with lower platelet count, and prolonged activated partial thromboplastin time (all p < 0.05). Malignancy was the most common etiology for pericardial effusion in both groups (28.6% in Antithrombotic Group and 54.7% in Non-antithrombotic Group). Tuberculosis was the second etiology in the Non-antithrombotic Group (21.9%), while procedure-related effusion (17.1%) accounted for the second cause in the Antithrombotic Group. Two patients in the Antithrombotic Group had mild oozing at the puncture site that resolved without interventions (2.9% vs 0%, p = 0.019), and no bleeding events higher than Grade 1 occurred in either group. Conclusion: Although antiplatelet or anticoagulant drugs may put patients undergoing pericardiocentesis at theoretically higher risk of bleeding, our study demonstrated that they are not associated with increased major bleeding complications.